Application of silica fume as water reducing agent, corresponding alkali-activated cementing material and preparation method of alkali-activated cementing material

By using silicon fume as a water reducer in alkali-excited gelling materials, the problem of insufficient fluidity and mechanical properties in the prior art is solved, efficient performance improvement and recycling of industrial waste are achieved, and costs are reduced.

CN119176685APending Publication Date: 2024-12-24GUANGDONG UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411102565.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

In the prior art, the water reducing agent of alkali-activated gelling materials has poor application effect in high-calcium and low-calcium systems, resulting in insufficient fluidity and mechanical properties, and the silicon fume cannot be effectively utilized as industrial waste, which is costly.

Method used

Silicone fume is used as a new water reducer to be used in alkali-excited gelling materials with fly ash-based low-calcium system and slag-based high-calcium system. The fluidity and mechanical properties of the material are improved by reacting with alkaline solutions.

Benefits of technology

The fluidity and compressive strength of alkali-activated gelled materials have been significantly improved. The use of silicon fume not only improves the material performance, but also realizes the recycling of industrial waste and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176685A_ABST
    Figure CN119176685A_ABST
Patent Text Reader

Abstract

The invention discloses application of silica fume as a water reducing agent, the water reducing agent is used for a coal ash-based low-calcium system alkali-activated cementing material and / or a slag-based high-calcium system alkali-activated cementing material, and discloses the coal ash-based low-calcium system alkali-activated cementing material, the slag-based high-calcium system alkali-activated cementing material and corresponding preparation methods. By doping silica fume as a water reducer, the expansion degree and compressive strength of the slag-based high-calcium system alkali-activated cementing material are obviously improved, the expansion degree reaches 236 mm and is improved by 30%, the compressive strength in 28 days can reach 104.6 MPa and is improved by 2%, the expansion degree and compressive strength of the fly ash-based low-calcium system alkali-activated cementing material are obviously improved, the expansion degree can reach 222.5 mm, and the compressive strength in 28 days can reach 104.6 MPa and is improved by 2%. The compressive strength can reach 58MPa, and the compressive strength is improved by 11.7%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new environmentally friendly low-carbon building materials, and relates to a new use of silica fume as a water reducing agent, as well as a fly ash-based low-calcium system alkali-activated cementitious material and a slag-based high-calcium system alkali-activated cementitious material prepared according to the use, and a preparation method of the corresponding alkali-activated cementitious material. Background Art

[0002] Alkali-activated cementitious materials (AAM) refer to precursor materials rich in Si-Al that undergo polymerization under the stimulation of alkaline solutions to produce inorganic polymers composed of Si-O-Al-O bonds. It has excellent mechanical properties, low shrinkage and good durability in corrosive environments. Compared with ordinary Portland cement (OPC), which produces a large amount of CO2 due to the calcination of raw materials (limestone, clay) during its production process, the amount of CO2 produced during the production process of AAM can be reduced by about 76%. In addition, the production of an average of 1700-1800 joules of energy per ton of OPC clinker. If AAM replaces OPC, energy consumption can be saved by 60%. Therefore, AAM is also considered to be a sustainable green cementitious material that can replace OPC in the future to reduce the high carbon emissions and high energy consumption caused by the cement industry. According to the different Ca content of the precursor material, AAM can be divided into a high-calcium system represented by alkali-activated slag (AAS) and a low-calcium system represented by alkali-activated fly ash (AAF). The high calcium system can generate CASH gel inside due to the high calcium content of the raw materials, and has a tobermorite-like structure. The low calcium system often forms NASH gel and a highly cross-linked, disordered pseudo-zeolite structure. Regardless of the system, the preparation of AAM can reduce the impact of OPC production on the environment while also achieving the purpose of recycling industrial waste.

[0003] Similar to OPC, the liquid-to-solid ratio can have a significant impact on the performance of AAM. According to research, the use of a lower liquid-to-solid ratio can significantly improve the mechanical properties of AAM. However, a too low liquid-to-solid ratio will lead to poor fluidity of the cementitious material, making it difficult to cast and form, affecting its engineering application. Therefore, in order to ensure excellent mechanical properties and working performance at the same time, the development and use of water reducers are particularly critical in the preparation process of concrete. Generally speaking, water reducers can increase the fluidity of cementitious materials while reducing the water-cement ratio, making it possible to prepare modern high-performance concrete. At present, the development and research of water reducers are mainly aimed at OPC and its concrete.

[0004] Traditional water reducers used in OPC systems have little effect on improving fluidity in AAM, and often lead to a decrease in its mechanical strength. This is mainly because most water reducers are unstable in a highly alkaline environment (PH>13), so when in contact with an alkali activator, their plasticizing function will be reduced and their chemical composition may change, and different precursor materials will also affect the effect of the water reducer. Taking polycarboxylates (PC) and naphthalene (N) as examples, which are the most widely used in the OPC concrete industry, for low-calcium system AAM (AAF), although polycarboxylates show better effects than naphthalene in improving working performance. However, in terms of mechanical properties, the addition of both can lead to a decrease in the compressive strength of AAF. For high-calcium system AAM (AAS), the addition of naphthalene can also significantly reduce the mechanical properties of AAS. Polycarboxylates have no obvious effect on improving working performance in the application of AAS prepared by water glass activated slag. But in general, traditional water reducers currently used in OPC systems can hardly play a good role in different AAM systems.

[0005] In recent years, borax and sodium hexametaphosphate have been found to have the potential to be new water reducers. Borax (B) is an inorganic compound with the molecular formula Na2B4O7·10H2O. It is usually a white powder containing colorless crystals and is easily soluble in water. In recent years, some scholars have noticed that it can significantly increase the working performance of AAF, a precursor material with high calcium fly ash, and is expected to become a new water reducer that can be used for AAM. Oderji used borax in the preparation of AAM with 85% F-class fly ash and 15% slag as precursor materials, and compared it with sodium triphosphate (STP), polycarboxylic acid, sodium gluconate (SG), calcium lignin sulfonate (CL), sodium lignin sulfonate (SL) and other materials. The results show that borax has a better effect on improving the performance of AAM than other water reducer materials, and significantly improves the compressive strength while improving the fluidity. In addition to borax, sodium hexametaphosphate (SH) can also reduce the liquid-solid ratio of hydrated magnesium silicate cement, and finally reduce the liquid-solid ratio to 0.4 at a 1% dosage, which increases the compressive strength of the sample to more than 70MPa after 90 days. However, so far, there are few studies on the application of borax and sodium hexametaphosphate as water reducers in different AAM systems, especially sodium hexametaphosphate, which has almost never been studied in AAM.

[0006] Silica fume (SF) is an industrial waste and a byproduct of the production of silicon metal and ferrosilicon alloys. It is a small spherical particle containing a large amount of glassy silica. According to statistics, the annual production of silica fume in the world is as high as 1 million tons. In order to promote the recycling of this industrial waste, silica fume is mainly used as an auxiliary cementitious material in the current building materials industry to mix with cement to prepare concrete. Generally speaking, the addition of silica fume to concrete often leads to a higher water demand. However, in previous studies by our research group, it was unexpectedly discovered that it may have the effect of being a water reducer in AAM.

[0007] Chinese patent CN105819719A discloses an enhanced geopolymer and a preparation method thereof, wherein phosphate and / or polyphosphate, high-density ore, fly ash, water glass, alkaline compounds, silicon dioxide, water and other raw materials are blended according to their weight proportions, the raw materials are ground and mixed into a uniform slurry, the slurry is injected into a mold, and the product is cured at room temperature or low temperature (20-80°C). The geopolymer product obtained by the formula and preparation method of the present invention is resistant to high temperature and chemicals, and has excellent mechanical properties, and its compressive strength reaches more than 150MPa, meeting the use requirements of building materials and high-temperature coatings.

[0008] CN116395998A discloses a 3D printable alkali-activated gelling material slurry, a product containing the same, and a preparation method and application thereof, wherein the alkali-activated gelling material slurry comprises an aluminosilicate precursor; an alkali activator comprising MOH, M2O·nSiO2 and H2O, wherein M is an alkali metal; and a modifier.

[0009] CN111548039A provides a red mud alkali activated cementitious material aggregate and a preparation method thereof, wherein the raw materials of the red mud alkali activated cementitious material aggregate include the following components by weight: 50-100 parts of red mud; 1-10 parts of activator; 0-40 parts of fly ash; and 20-60 parts of water. The red mud alkali activated cementitious material aggregate has high mechanical properties and compressive strength and has a wider range of engineering applications.

[0010] and US9,266,783 discloses a tailor-made precursor material composition in solid form of geopolymer material comprising fly ash (59-91%), sodium hydroxide (11-15%), rice husk (0.8-11%) and optionally sodium silicate (0-29%), however its mechanical properties need to be improved.

[0011] US2009 / 0229493A1 discloses a high compressibility silica mortar composed of 30 to 70 weight percent silica, 40 to 70 weight percent blast furnace slag, and 100 weight percent of dry mortar powder of these silicas with 15 to 35 weight percent of polycondensation regulator, slag, and by generating C-S-H, CAH, amorphous Geopolymeric Matrix {Al2O3·mSiO2·nM2O.xH2O (M = K, Na, Ca)} and zeolite. The characteristics of the high-strength silica mortar are that after vibrating and forming and curing for 12 to 48 hours at 25 to 80°C, it shows a compressive strength of more than 70.0MPa, and it is cured for 12 to 48 hours before removing the form and aging for 28 days, which can save energy. However, it contains a large amount of silica and is very costly.

[0012] And US8,440,016B2 discloses a ground granulated blast furnace slag for sulfate-resistant cement, which comprises a mixture of ground granulated blast furnace slag with an alumina content of 12 to 17.5% by mass and high-solubility gypsum with 2 to 6% by mass of gypsum, which can be used for concrete mortar.

[0013] and US20130081557A1 discloses a system, method and / or composition of an environmentally friendly composite building material. In one aspect, a method includes providing a mixture of volcanic ash material and / or kaolin clay with an activator solution to form an aluminosilicate cementitious material through a resulting geopolymerization process. The aluminosilicate cementitious material is in a paste form. The method also includes processing the aluminosilicate cementitious material to convert the silicate cementitious material into the form of an aluminosilicate cementitious material powder. The method further includes mixing the aluminosilicate cementitious material in powder form with water to control the processability of the aluminosilicate cementitious material.

[0014] The above-mentioned alkali-activated cementitious materials based on slag-based high-calcium system and fly ash-based low-calcium system all have certain defects in mechanical properties and the content of silicon dioxide is too high, resulting in high costs and unable to truly achieve low-cost concrete. The present invention is based on silica fume (SFU) as an admixture. Due to its good insulation and corrosion resistance, it is widely used in the concrete industry. However, at present, there is almost no research on its application as a water reducer in alkali-activated cementitious materials. Therefore, this study uses SFU as a water reducer to explore its effect, application and preparation method in alkali-activated cementitious materials based on slag-based high-calcium system and fly ash-based low-calcium system. Summary of the invention

[0015] The object of the present invention is to provide a use of silica fume as a water reducing agent and a corresponding alkali-activated cementitious material to solve the above-mentioned background problems.

[0016] The purpose of the present invention can be achieved through the following technical solutions: In a first aspect, the present application proposes a use of silica fume as a water reducer, wherein the silica fume is used as a water reducer for a low-calcium-alkali activated cementitious material system and / or a high-calcium-alkali activated cementitious material system.

[0017] Furthermore, the low-calcium alkali activated cementitious material system is a fly ash-based low-calcium alkali activated cementitious material system and or the high-calcium high-calcium alkali activated cementitious material system is a slag-based high-calcium alkali activated cementitious material system.

[0018] Furthermore, the silica fume is used as a water reducing agent in fly ash-based low-calcium alkali-activated cementitious materials and slag-based high-calcium alkali-activated cementitious materials.

[0019] Furthermore, the silica fume is amorphous SiO2, the average particle size of the silica fume is about 0.1-0.3 μm, and the specific surface area ranges from 15 to 30 m 2 / g; At room temperature, the silica fume is insoluble in water but soluble in alkali, and can react with hydrofluoric acid aqueous solution. The differential thermal analysis curve of the silica fume shows that when heated to above 500°C, amorphous SiO2 is transformed into crystalline SiO2, and the crystalline SiO2 is cristobalite and / or tridymite.

[0020] In the second aspect, the present application discloses a fly ash-based low-calcium system alkali-activated cementitious material; the alkali-activated cementitious material is prepared from the following materials: a water reducer, an alkali-activated cementitious material precursor material - Class F fly ash, and an alkali solution.

[0021] Furthermore, the water reducer can be selected from one or more of naphthalene-based water reducer, borax, sodium hexametaphosphate, polycarboxylic acid, silica sand, and silica fume.

[0022] Furthermore, the water reducing agent is silica fume, and the silica fume is amorphous (non-crystalline) SiO2, and the average particle size of the silica fume is about 0.1-0.3 μm, and the specific surface area ranges from 15 to 30 m 2 / g; At room temperature, the silica fume is insoluble in water but soluble in alkali, and can react with hydrofluoric acid aqueous solution. The differential thermal analysis curve of the silica fume shows that when heated to above 500°C, amorphous SiO2 is transformed into crystalline SiO2, and the crystalline SiO2 is cristobalite and / or tridymite.

[0023] The silica fume particle size distribution is as follows: Figure 5 As shown, the silica fume is active silica fume.

[0024] Furthermore, the alkaline solution includes sodium silicate solution and sodium hydroxide solution.

[0025] Further, in parts by mass, the water reducer is 0.01-12 parts, the alkali-activated cementitious material precursor material - F-type fly ash is 80-150 parts, the sodium silicate solution is 20-35 parts, and the sodium hydroxide solution is 8-15 parts; preferably, the water reducer is 0.5-8 parts, the alkali-activated cementitious material precursor material - F-type fly ash is 95-105 parts, the sodium silicate solution is 25-30 parts, and the sodium hydroxide solution is 9-12 parts; more preferably, the water reducer is 0.5-6 parts, the alkali-activated cementitious material precursor material - F-type fly ash is 95-105 parts, the sodium silicate solution is 25-30 parts, and the sodium hydroxide solution is 9-12 parts. The precursor material - Class F fly ash is 100 parts, the sodium silicate solution is 27.1 parts, and the sodium hydroxide solution is 10.9 parts; more preferably, the water reducer is 2-5 parts, the alkali-activated cementitious material precursor material - Class F fly ash is 100 parts, the sodium silicate solution is 27.1 parts, and the sodium hydroxide solution is 10.9 parts; more preferably, the water reducer is 3-4 parts, the alkali-activated cementitious material precursor material - Class F fly ash is 100 parts, the sodium silicate solution is 27.1 parts, and the sodium hydroxide solution is 10.9 parts.

[0026] Furthermore, the F-type fly ash is the only precursor material for preparing alkali-activated cementitious materials, and the mass percentage of each oxide in its chemical composition is: SiO2 (54.17%), Al2O3 (31.57%), Fe2O3 (3.48%), CaO (2.98%), K2O (1.90%), TiO2 (1.37%), MgO (1.22%) and others (3.31%). The F-type fly ash has the following properties: Figure 4 Particle size distribution.

[0027] Furthermore, the sodium silicate solution is used to prepare an alkali-activated solution, wherein SiO2 accounts for 27.3%, Na2O accounts for 8.54%, and the modulus is 3.3; the sodium hydroxide solution is used to prepare an alkali-activated solution, which is a liquid with a concentration of 10-20M prepared by using solid sodium hydroxide particles with a purity of ≥96%; preferably, the concentration is 14M.

[0028] Furthermore, the sodium hydroxide solution can be replaced by other solutions such as potassium hydroxide or other highly soluble alkali metal hydroxide salts.

[0029] Furthermore, the fluidity of the fly ash-based low-calcium alkali-activated cementitious material has an extension of not less than 200 mm, and a compressive strength of up to 58 MPa; and the compressive strength of the alkali-activated cementitious material can be improved without reducing the fluidity.

[0030] In a third aspect, the present application discloses a method for preparing a fly ash-based low-calcium system alkali-activated cementitious material, comprising the following steps: (1) Weigh 0.01-12 parts of water reducer and 80-150 parts of alkali-activated cementitious material precursor material - Class F fly ash according to the mass fraction respectively, and use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.01g; (2) Mix the weighed water reducer and the alkali-activated cementitious material precursor material - Class F fly ash into a mixer and stir until uniform; (3) Weighing materials according to 20-35 parts of sodium silicate solution and 8-15 parts of 10-20M sodium hydroxide solution, using an electronic balance to weigh the materials, and the weighing balance accuracy of the materials is ±0.01g; the chemical composition of the sodium silicate solution is 27.3% SiO2, 8.54% Na2O, and the modulus is 3.3; (4) preparing an alkaline solution by mixing the sodium silicate solution in step (3) and a 10-20 M sodium hydroxide solution and stirring them uniformly; (5) Pour the alkaline solution prepared in step (4) into the fly ash and powdered water reducing agent mixed in step (2), and stir at level 5 for 3 minutes using a mixer until a completely uniform paste appears.

[0031] Furthermore, after step (5), the method further includes the following steps: (6) using a cement mortar fluidity tester (referred to as a jump table) to perform a fluidity test on the paste-like alkali-activated cementitious material stirred in step (5) in accordance with the ASTM C230 cement mortar fluidity test method; (7) Select the dosage with the best fluidity to prepare the alkali-activated cementitious material test blocks and test the compressive strength.

[0032] Furthermore, the water reducing agent is silica fume, and the silica fume powder is a spherical white powder with a purity of >99% and a particle size distribution as follows: Figure 5 shown.

[0033] Furthermore, the water reducing agent is 0.5-8 parts, the alkali-activated cementitious material precursor material - F-type fly ash is 95-105 parts, the sodium silicate solution is 25-30 parts, and the sodium hydroxide solution is 9-12 parts.

[0034] Furthermore, the water reducing agent is 0.5-6 parts, the alkali-activated cementitious material precursor material - F-type fly ash is 100 parts, the sodium silicate solution is 27.1 parts, and the 10-20M sodium hydroxide solution is 10.9 parts.

[0035] Furthermore, the F-type fly ash is the only precursor material for preparing alkali-activated cementitious materials, and the mass percentage of each oxide in its chemical composition is: SiO2 (54.17%), Al2O3 (31.57%), Fe2O3 (3.48%), CaO (2.98%), K2O (1.90%), TiO2 (1.37%), MgO (1.22%) and others (3.31%). The F-type fly ash has the following properties: Figure 4 Particle size distribution.

[0036] Furthermore, the sodium silicate solution is used to prepare an alkali-activated solution, wherein SiO2 accounts for 27.3%, Na2O accounts for 8.54%, and the modulus is 3.3; the sodium hydroxide solution is used to prepare an alkali-activated solution, which is a liquid with a concentration of 10-20M prepared by using solid sodium hydroxide particles with a purity of ≥96%; preferably, the concentration is 14M.

[0037] Fourthly, the present application requests protection for the use of silica fume as a water reducer for fly ash-based low-calcium system alkali-activated cementitious materials, wherein the fly ash in the fly ash-based low-calcium system alkali-activated cementitious materials is Class F fly ash.

[0038] Furthermore, the fly ash-based low-calcium alkali-activated cementitious material is the fly ash-based low-calcium alkali-activated cementitious material of the second aspect of the present application.

[0039] In a fifth aspect, the present application provides a slag-based high-calcium system alkali-activated cementitious material using silica fume as a water reducer; the alkali-activated cementitious material is prepared from the following materials: a water reducer, an alkali-activated cementitious material precursor material - S95 grade slag, and an alkali solution.

[0040] Furthermore, the water reducing agent is silica fume, and the silica fume is amorphous (non-crystalline) SiO2, and the average particle size of the silica fume is about 0.1-0.3 μm, and the specific surface area ranges from 15 to 30 m 2 / g; At room temperature, the silica fume is insoluble in water but soluble in alkali, and can react with hydrofluoric acid aqueous solution. The differential thermal analysis curve of the silica fume shows that when heated to above 500°C, amorphous SiO2 is transformed into crystalline SiO2, and the crystalline SiO2 is cristobalite and / or tridymite.

[0041] The silica fume particle size distribution is as follows: Figure 5 As shown, the silica fume is active silica fume.

[0042] Furthermore, the alkaline solution includes sodium silicate solution and sodium hydroxide solution.

[0043] Furthermore, in parts by mass, the water reducer is 0.01-12 parts, the alkali-activated cementitious material precursor material - S95 grade slag is 80-150 parts, the sodium silicate solution is 8-20 parts, and the sodium hydroxide solution is 14-28 parts; Preferably, the water reducer is 0.5-8 parts, the alkali-activated cementitious material precursor material - S95 grade slag is 95-105 parts, the sodium silicate solution is 10-16 parts, and the sodium hydroxide solution is 16-22 parts; More preferably, the water reducing agent is 0.5-6 parts, the alkali-activated cementitious material precursor material - S95 grade slag is 100 parts, the sodium silicate solution is 14.6 parts, and the sodium hydroxide solution is 20.4 parts; More preferably, the water reducing agent is 2-5 parts, the alkali-activated cementitious material precursor material - S95 grade slag is 100 parts, the sodium silicate solution is 14.6 parts, and the sodium hydroxide solution is 20.4 parts; More preferably, the water reducing agent is 3-4 parts, the alkali-activated cementitious material precursor material - S95 grade slag is 100 parts, the sodium silicate solution is 14.6 parts, and the sodium hydroxide solution is 20.4 parts.

[0044] Furthermore, the alkali-activated cementitious material precursor material-S95 grade slag is the only precursor material for preparing the alkali-activated cementitious material, and the mass percentage of each oxide in its chemical composition is: CaO (40.43%), SiO2 (30.46%), Al2O3 (15.81%), MgO (9.42%), Fe2O3 (0.281%), K2O (0.423%), TiO2 (0.673%), M nO (0.52%), Na2O (0.499%), S (1.16%), SrO (0.0549%), Cl (0.0467%), ZrO2 (0.0391%), BaO (0 .0389%), P2O5 (0.017%), V2O5 (0.0084%), Y2O3 (0.0083%), CeO2 (0.0069%), CuO (0.0012%).

[0045] Furthermore, the sodium silicate solution is used to prepare an alkali-activated solution, and the chemical composition of the sodium silicate solution includes 27.3% SiO2, 8.54% Na2O, and a modulus of 3.3; the sodium hydroxide solution is used to prepare an alkali-activated solution, which is prepared using sodium hydroxide solid particles with a purity of ≥96%, including 1.8 parts of sodium hydroxide particles and 18.6 parts of distilled water.

[0046] Furthermore, the sodium hydroxide solution can be replaced by other solutions such as potassium hydroxide or other highly soluble alkali metal hydroxide salts.

[0047] Furthermore, the fluidity of the slag-based high-calcium system alkali-activated cementitious material has an extension of not less than 236 mm, and a compressive strength of up to 104.6 MPa; the compressive strength of the alkali-activated cementitious material can be improved without reducing the fluidity.

[0048] In a sixth aspect, the present application discloses a method for preparing a slag-based high-calcium system alkali-activated cementitious material using silica fume as a water reducer, comprising the following steps: (1) Weigh 0.01-12 parts of water reducer and 80-150 parts of alkali-activated cementitious material precursor material - S95 grade slag according to the mass fraction respectively, and use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.01g; (2) Mix the weighed water reducer and the alkali-activated cementitious material precursor material - S95 grade slag into a mixer and stir until uniform; (3) Weighing materials according to 8-20 parts of sodium silicate solution and 14-28 parts of sodium hydroxide solution, using an electronic balance to weigh the materials, and the weighing balance accuracy of the materials is ±0.01g; the chemical composition of the sodium silicate solution is 27.3% SiO2, 8.54% Na2O, and the modulus is 3.3; (4) preparing an alkaline solution by mixing the sodium silicate solution and the sodium hydroxide solution in step (3) and stirring them uniformly; (5) Pour the alkaline solution prepared in step (4) into the alkali-activated cementitious material precursor material (S95 grade slag and powdered water reducer) mixed in step (2), and stir at level 5 speed for 3 minutes using a mixer until a completely uniform paste is formed.

[0049] Furthermore, after step (5), the method further includes the following steps: (6) using a cement mortar fluidity tester (referred to as a jump table) to perform a fluidity test on the paste-like alkali-activated cementitious material stirred in step (5) in accordance with the ASTM C230 cement mortar fluidity test method; (7) Select the dosage with the best fluidity to prepare the alkali-activated cementitious material test blocks and test the compressive strength.

[0050] Furthermore, the water reducing agent is silica fume, which is a spherical white powder with a purity of more than 99% and a particle size distribution as follows: Figure 5 As shown, the silica fume is active silica fume.

[0051] Furthermore, in parts by mass, the water reducer is 0.01-12 parts, the alkali-activated cementitious material precursor material - S95 grade slag is 80-150 parts, the sodium silicate solution is 8-20 parts, and the sodium hydroxide solution is 14-28 parts.

[0052] Preferably, the water reducing agent is 0.5-8 parts, the alkali-activated cementitious material precursor material - S95 grade slag is 95-105 parts, the sodium silicate solution is 10-16 parts, and the sodium hydroxide solution is 16-22 parts.

[0053] More preferably, the water reducing agent is 0.5-6 parts, the alkali-activated cementitious material precursor material - S95 grade slag is 100 parts, the sodium silicate solution is 14.6 parts, and the sodium hydroxide solution is 20.4 parts.

[0054] More preferably, the water reducing agent is 2-5 parts, the alkali-activated cementitious material precursor material - S95 grade slag is 100 parts, the sodium silicate solution is 14.6 parts, and the sodium hydroxide solution is 20.4 parts.

[0055] More preferably, the water reducing agent is 3-4 parts, the alkali-activated cementitious material precursor material - S95 grade slag is 100 parts, the sodium silicate solution is 14.6 parts, and the sodium hydroxide solution is 20.4 parts.

[0056] Furthermore, the alkali-activated cementitious material precursor material - S95 grade slag is the only precursor material for preparing the alkali-activated cementitious material, and the mass percentage of each oxide in its chemical composition is: CaO (40.43%), SiO2 (30.46%), Al2O3 (15.81%), MgO (9.42%), Fe2O3 (0.281%), K2O (0.423%), TiO2 (0.673%), MnO (0.52%), Na2O (0.499%), S (1.16%), SrO (0.0549%), Cl (0.0467%), ZrO2 (0.0391%), BaO (0.0389%), P2O5 (0.017%), V2O5 (0.0084%), Y2O3 (0.0083%), CeO2 (0.0069%), CuO (0.0012%), the alkali activated cementitious material precursor material - S95 grade slag has the following characteristics: Figure 4 Particle size distribution.

[0057] Furthermore, the sodium silicate solution is used to prepare an alkali-activated solution, wherein SiO2 accounts for 27.3%, Na2O accounts for 8.54%, and the modulus is 3.3 in the chemical composition of the sodium silicate solution; the sodium hydroxide solution is used to prepare an alkali-activated solution, which is prepared using sodium hydroxide solid particles with a purity of ≥96% and a concentration of 1.8 parts of sodium hydroxide particles and 18.6 parts of distilled water.

[0058] In a seventh aspect, the present application discloses a use of silica fume as a water reducer for a slag-based high-calcium system alkali-activated cementitious material, wherein the slag in the slag-based high-calcium system alkali-activated cementitious material is S95 grade slag.

[0059] Furthermore, the slag-based high-calcium system alkali-activated cementitious material is the slag-based high-calcium system alkali-activated cementitious material of the fifth aspect of the present application.

[0060] Beneficial effects of the present invention: (1) Silica fume was first discovered to be used as a water reducer for fly ash-based low-calcium alkali-activated cementitious materials and slag-based high-calcium alkali-activated cementitious materials.

[0061] (2) Compared with several other relatively mature high-efficiency water reducers (naphthalene series, polycarboxylic acid, borax, sodium hexametaphosphate), silica fume has a better effect in improving the flow properties of fly ash-based alkali-activated cementitious materials. The flow properties can be increased by 40.8% compared with other water reducers.

[0062] (3) Compared with several other relatively mature high-efficiency water reducers (naphthalene series, polycarboxylic acid, borax, sodium hexametaphosphate), silica fume has a better effect in improving the mechanical properties of fly ash-based alkali-activated cementitious materials. The compressive strength can reach 68.3MPa.

[0063] (4) Compared with several other relatively mature high-efficiency water reducers (naphthalene series, polycarboxylic acid, borax, sodium hexametaphosphate), silica fume has a better effect in improving the fluidity of slag-based high-calcium system alkali-activated cementitious materials. The fluidity can be increased by 50% when the addition amount is 3% compared with other water reducers.

[0064] (5) Compared with several other relatively mature high-efficiency water reducers (naphthalene, polycarboxylic acid, borax, sodium hexametaphosphate), silica fume has a better effect in improving the mechanical properties of slag-based high-calcium system alkali-activated cementitious materials. The appropriate addition amount can increase the compressive strength to 70.7MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] The present invention will be further described below in conjunction with the accompanying drawings.

[0066] Figure 1 This is a flow chart for preparing the fly ash-based low-calcium system alkali-activated cementitious material of the present invention; Figure 2 This is a graph showing the fluidity test results of the fly ash-based low-calcium system alkali-activated gelling material of the present invention; Figure 3 This is a graph showing the compressive strength test results of the fly ash-based low-calcium system alkali-activated cementitious material of the present invention; Figure 4 is a fly ash particle size distribution diagram of the present invention; Figure 5 is a scanning electron microscope image of each raw material of the present invention; Figure 6This is a flow chart for preparing the slag-based high-calcium system alkali-activated cementitious material of the present invention; Figure 7 This is a graph showing the fluidity test results of the slag-based high-calcium system alkali-activated gelling material of the present invention; Figure 8 This is a graph showing the compressive strength test results of the slag-based high-calcium system alkali-activated cementitious material of the present invention; Fig. 9 It is the particle size distribution diagram of S95 grade slag of the present invention. DETAILED DESCRIPTION

[0067] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0068] In a specific embodiment, the silica fume is amorphous SiO2, the average particle size of the silica fume is about 0.1-0.3 μm, and the specific surface area ranges from 15 to 30 m 2 / g; At room temperature, the silica fume is insoluble in water but soluble in alkali, and can react with hydrofluoric acid aqueous solution. The differential thermal analysis curve of the silica fume shows that when heated to above 500°C, amorphous SiO2 is transformed into crystalline SiO2, and the crystalline SiO2 is cristobalite and / or tridymite.

[0069] Silica fume particle size distribution Figure 5 As shown, the silica fume is active silica fume purchased from Kegong Metallurgical Company. It is spherical white powder with a purity of >99%.

[0070] Silica sand is inert silica sand purchased from Beasley New Materials Company, with a purity of >99%, and is a white spherical powder.

[0071] A fly ash-based low-calcium alkali-activated cementitious material is formulated according to the following weight parts: (1) 100 parts of Class F fly ash; (2) 27.1 parts of sodium silicate solution; and (3) 10.9 parts of sodium hydroxide solution (14M).

[0072] Wherein, the particle size distribution of the F type fly ash is as follows: Figure 4The mass percentage of each oxide in its chemical composition is: SiO2 (54.17%), Al2O3 (31.57%), Fe2O3 (3.48%), CaO (2.98%), K2O (1.90%), TiO2 (1.37%), MgO (1.22%) and others (3.31%).

[0073] Among them, the sodium silicate solution is produced by Jiashan County Yourui Refractory Materials Co., Ltd., and its chemical composition includes SiO2 accounting for 27.3%, Na2O accounting for 8.54%, and the modulus is 3.3.

[0074] The sodium hydroxide solution is a liquid with a concentration of 14M prepared from solid sodium hydroxide particles with a purity of ≥96%.

[0075] A method for preparing a fly ash-based low-calcium system alkali-activated cementitious material, such as Figure 1 As shown, the following steps are included: (1) Weigh the material according to 100 parts of fly ash using an electronic balance with an accuracy of ±0.01g; (2) Weigh the material according to 27.1 parts of sodium silicate solution and 10.9 parts of sodium hydroxide solution (14M). Use an electronic balance to weigh the material. The weighing balance accuracy of the material is ±0.01g; (3) preparing an alkaline solution by mixing 27.1 parts of sodium silicate solution and 10.9 parts of sodium hydroxide solution (14 M) and stirring until uniform; (4) Pour the alkaline solution prepared in step (3) into the fly ash weighed in step (1), and stir at level 5 for 3 minutes using a stirrer until a completely uniform paste is formed; (5) Using a cement mortar fluidity tester (referred to as a jump table), the fluidity of the paste-like alkali-activated cementitious material stirred in step (5) is tested in accordance with the ASTM C230 cement mortar fluidity test method.

[0076] Since the material used in the blank example is a fly ash-based low-calcium alkali-activated cementitious material, it is named AAF.

[0077] Example 1: The components, weight parts and test methods of the water reducing agent used for low-calcium alkali-activated cementitious materials in this example are the same as those in the blank example, except that 0.5 parts of silica fume is added as the water reducing agent.

[0078] The silica fume was purchased from the Science and Technology Metallurgical Company and was a spherical white powder with a purity of >99%.

[0079] The above materials were tested according to the following steps to obtain a water reducing agent suitable for low-calcium system alkali-activated cementitious materials, such as Figure 1As shown, the following steps are included: (1) Weigh the materials according to 0.5 parts of silica fume and 100 parts of fly ash. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.01g; (2) Mix the weighed powdered water reducer and the alkali-activated cementitious material precursor - fly ash into a mixer and stir at level 2 speed for 1 minute until uniform; (3) Weigh the materials according to 27.1 parts of sodium silicate solution and 10.9 parts of sodium hydroxide solution (14M). Use an electronic balance to weigh the materials. The weighing accuracy of the material is ±0.01g. (4) preparing an alkaline solution by mixing 27.1 parts of sodium silicate solution and 10.9 parts of sodium hydroxide solution (14 M) and stirring them uniformly; (5) Pour the alkaline solution prepared in step (4) into the fly ash and powdered water reducing agent mixed in step (2), and stir at level 5 for 3 minutes using a mixer until a completely uniform paste is formed; (6) Using a cement mortar fluidity tester (referred to as a jump table), the fluidity of the paste-like alkali-activated cementitious material mixed in step (5) is tested in accordance with the ASTM C230 cement mortar fluidity test method.

[0080] Since the water reducing agent used in Example 1 is silica fume with a dosage of 0.5%, it is named SFU-0.5%.

[0081] Example 2: The components, mass parts and test methods of the water reducer used in the low-calcium alkali-activated cementitious materials in this example are the same as those in the blank example, and the test steps are the same as those in Example 1, except that silica fume is added as a water reducer, with the amount of silica fume being 1 part.

[0082] Since the water reducing agent used in Example 2 is silica fume with a dosage of 1%, it is named SFU-1%.

[0083] Example 3: The components, mass parts and test methods of the water reducer used in the low-calcium alkali-activated cementitious materials in this example are the same as those in the blank example, and the test steps are the same as those in Example 1, except that 2 parts of silica fume are added as the water reducer.

[0084] Since the water reducing agent used in Example 3 is silica fume with a dosage of 2%, it is named SFU-2%.

[0085] Example 4: The components and their mass parts and testing methods of the water reducer used for low-calcium alkali-activated cementitious materials in this example are the same as those in the blank example, and the testing steps are the same as those in Example 1, except that 3 parts of silica fume are added as the water reducer.

[0086] Since the water reducing agent used in Example 4 is silica fume with a dosage of 3%, it is named SFU-3%.

[0087] Example 5: The components, mass parts and test methods of the water reducer used in the low-calcium alkali-activated cementitious materials in this example are the same as those in the blank example, and the test steps are the same as those in Example 1, except that 4 parts of silica fume are added as the water reducer.

[0088] Since the water reducing agent used in Example 5 is silica fume with a dosage of 4%, it is named SFU-4%.

[0089] Example 6: The components, mass parts and test methods of the water reducer used in the low-calcium alkali-activated cementitious materials in this example are the same as those in the blank example, and the test steps are the same as those in Example 1, except that 5 parts of silica fume are added as the water reducer.

[0090] Since the water reducing agent used in Example 6 is silica fume with a dosage of 5%, it is named SFU-5%.

[0091] Example 7: The components, mass parts and test methods of the water reducer used in the low-calcium alkali-activated cementitious materials in this example are the same as those in the blank example, and the test steps are the same as those in Example 1, except that 6 parts of silica fume are added as the water reducer.

[0092] Since the water reducing agent used in Example 7 is silica fume with a dosage of 6%, it is named SFU-6%.

[0093] Comparative Example 1: The weight parts, test steps and methods of the water reducer that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 1, except that the silica fume is replaced by a naphthalene-based water reducer.

[0094] Among them, the naphthalene-based water reducer was purchased from Shanghai Chenqi Chemical Technology Co., Ltd., model number is CQJ-NX, and the appearance is brown-yellow powder.

[0095] Since the water reducer used in Comparative Example 1 is a naphthalene-based water reducer with a dosage of 0.5%, it is named N-0.5%.

[0096] Comparative Example 2: The weight parts, test steps and methods of the water reducer that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 2, except that the silica fume is replaced by a naphthalene-based water reducer.

[0097] Since the water reducer used in Comparative Example 2 is a naphthalene-based water reducer with a dosage of 1%, it is named N-1%.

[0098] Comparative Example 3: The weight parts, test steps and methods of the water reducer that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 3, except that the silica fume is replaced by a naphthalene-based water reducer.

[0099] Since the water reducer used in Comparative Example 3 is a naphthalene-based water reducer with a dosage of 2%, it is named N-2%.

[0100] Comparative Example 4: The weight parts, test steps and methods of the water reducer that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 4, except that the silica fume is replaced by a naphthalene-based water reducer.

[0101] Since the water reducer used in Comparative Example 4 is a naphthalene-based water reducer with a dosage of 3%, it is named N-3%.

[0102] Comparative Example 5: The weight parts, test steps and methods of the water reducer that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 5, except that the silica fume is replaced by a naphthalene-based water reducer.

[0103] Since the water reducer used in Comparative Example 5 is a naphthalene-based water reducer with a dosage of 4%, it is named N-4%.

[0104] Comparative Example 6: The weight parts, test steps and methods of the water reducer that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 6, except that the silica fume is replaced by a naphthalene-based water reducer.

[0105] Since the water reducer used in Comparative Example 6 is a naphthalene-based water reducer with a dosage of 5%, it is named N-5%.

[0106] Comparative Example 7: The weight parts, test steps and methods of the water reducer that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 7, except that the silica fume is replaced by a naphthalene-based water reducer.

[0107] Since the water reducer used in Comparative Example 7 is a naphthalene-based water reducer with a dosage of 6%, it is named N-6%.

[0108] Comparative Example 8: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 1, except that the silica fume is replaced by borax.

[0109] Among them, borax was purchased from Sinopharm Chemical Reagent Co., Ltd., with the chemical formula of Na2B4O7·10H2O, and is a colorless, transparent crystalline powder.

[0110] Since the water reducing agent used in Comparative Example 8 is borax with a dosage of 0.5%, it is named B-0.5%.

[0111] Comparative Example 9: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 2, except that the silica fume is replaced by borax.

[0112] Since the water reducing agent used in Comparative Example 9 is borax with a dosage of 1%, it is named B-1%.

[0113] Comparative Example 10: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 3, except that the silica fume is replaced by borax.

[0114] Since the water reducing agent used in Comparative Example 10 is borax with a dosage of 2%, it is named B-2%.

[0115] Comparative Example 11: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 4, except that the silica fume is replaced by borax.

[0116] Since the water reducing agent used in Comparative Example 11 is borax with a dosage of 3%, it is named B-3%.

[0117] Comparative Example 12: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 5, except that the silica fume is replaced by borax.

[0118] Since the water reducing agent used in Comparative Example 12 is borax with a dosage of 4%, it is named B-4%.

[0119] Comparative Example 13: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 6, except that the silica fume is replaced by borax.

[0120] Since the water reducing agent used in Comparative Example 13 is borax with a dosage of 5%, it is named B-5%.

[0121] Comparative Example 14: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 7, except that the silica fume is replaced by borax.

[0122] Since the water reducing agent used in Comparative Example 14 is borax with a dosage of 6%, it is named B-6%.

[0123] Comparative Example 15: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 1, except that the silica fume is replaced by sodium hexametaphosphate.

[0124] Among them, sodium hexametaphosphate is produced by Xilong Chemical Company, analytically pure, and is in the form of colorless, transparent glass flakes or micro-particle crystals.

[0125] Since the water reducing agent used in Comparative Example 15 is sodium hexametaphosphate and the dosage is 0.5%, it is named SH-0.5%.

[0126] Comparative Example 16: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 2, except that the silica fume is replaced by sodium hexametaphosphate.

[0127] Since the water reducer used in Comparative Example 16 is sodium hexametaphosphate and the dosage is 1%, it is named SH-1%.

[0128] Comparative Example 17: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 3, except that the silica fume is replaced by sodium hexametaphosphate.

[0129] Since the water reducing agent used in Comparative Example 17 is sodium hexametaphosphate and the dosage is 2%, it is named SH-2%.

[0130] Comparative Example 18: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 4, except that the silica fume is replaced by sodium hexametaphosphate.

[0131] Since the water reducing agent used in Comparative Example 18 is sodium hexametaphosphate and the dosage is 3%, it is named SH-3%.

[0132] Comparative Example 19: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 5, except that the silica fume is replaced by sodium hexametaphosphate.

[0133] Since the water reducing agent used in Comparative Example 19 is sodium hexametaphosphate and the dosage is 4%, it is named SH-4%.

[0134] Comparative Example 20: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 6, except that the silica fume is replaced by sodium hexametaphosphate.

[0135] Since the water reducer used in Comparative Example 20 is sodium hexametaphosphate and the dosage is 5%, it is named SH-5%.

[0136] Comparative Example 21: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 7, except that the silica fume is replaced with sodium hexametaphosphate.

[0137] Since the water reducer used in Comparative Example 21 is sodium hexametaphosphate with a dosage of 6%, it is named SH-6%.

[0138] Comparative Example 22: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 1, except that the silica fume is replaced by polycarboxylic acid.

[0139] Among them, polycarboxylic acid was purchased from Shanghai Chenqi Chemical Technology Co., Ltd., Sika brand, model 540P, white solid powder.

[0140] Since the water reducer used in Comparative Example 22 is polycarboxylic acid with a dosage of 0.5%, it is named PC-0.5%.

[0141] Comparative Example 23: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 2, except that the silica fume is replaced by polycarboxylic acid.

[0142] Since the water reducer used in Comparative Example 23 is polycarboxylic acid with a dosage of 1%, it is named PC-1%.

[0143] Comparative Example 24: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 3, except that the silica fume is replaced by polycarboxylic acid.

[0144] Since the water reducer used in Comparative Example 24 is polycarboxylic acid with a dosage of 2%, it is named PC-2%.

[0145] Comparative Example 25: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 4, except that the silica fume is replaced by polycarboxylic acid.

[0146] Since the water reducer used in Comparative Example 25 is polycarboxylic acid with a dosage of 3%, it is named PC-3%.

[0147] Comparative Example 26: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 5, except that the silica fume is replaced by polycarboxylic acid.

[0148] Since the water reducer used in Comparative Example 26 is polycarboxylic acid with a dosage of 4%, it is named PC-4%.

[0149] Comparative Example 27: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 6, except that the silica fume is replaced by polycarboxylic acid.

[0150] Since the water reducer used in Comparative Example 27 is polycarboxylic acid with a dosage of 5%, it is named PC-5%.

[0151] Comparative Example 28: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 7, except that the silica fume is replaced by polycarboxylic acid.

[0152] Since the water reducer used in Comparative Example 28 is polycarboxylic acid with a dosage of 6%, it is named PC-6%.

[0153] Comparative Example 29: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 1, except that the silica fume is replaced by silica sand.

[0154] The silica sand was purchased from Beasley New Materials Company, with a purity of >99% and a white spherical powder.

[0155] Since the water reducing agent used in Comparative Example 29 is silica sand with a dosage of 0.5%, it is named SFL-0.5%.

[0156] Comparative Example 30: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 2, except that the silica fume is replaced by silica sand.

[0157] Since the water reducing agent used in Comparative Example 30 is silica sand with a dosage of 1%, it is named SFL-1%.

[0158] Comparative Example 31: The weight parts, testing steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 3, except that the silica fume is replaced by silica sand.

[0159] Since the water reducing agent used in Comparative Example 31 is silica sand with a dosage of 2%, it is named SFL-2%.

[0160] Comparative Example 32: The weight parts, testing steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 4, except that the silica fume is replaced by silica sand.

[0161] Since the water reducing agent used in Comparative Example 32 is silica sand with a dosage of 3%, it is named SFL-3%.

[0162] Comparative Example 33: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 5, except that the silica fume is replaced by silica sand.

[0163] Since the water reducing agent used in Comparative Example 33 is silica sand with a dosage of 4%, it is named SFL-4%.

[0164] Comparative Example 34: The weight parts, test steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 6, except that the silica fume is replaced by silica sand.

[0165] Since the water reducing agent used in Comparative Example 34 is silica sand with a dosage of 5%, it is named SFL-5%.

[0166] Comparative Example 35: The weight parts, testing steps and methods of the water reducing agent that can be used for low-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 7, except that the silica fume is replaced by silica sand.

[0167] Since the water reducing agent used in Comparative Example 35 is silica sand with a dosage of 6%, it is named SFL-6%.

[0168] A fly ash-based low-calcium alkali-activated cementitious material is formulated according to the following weight parts: (1) 100 parts of Class F fly ash; (2) 27.1 parts of sodium silicate solution; and (3) 10.9 parts of sodium hydroxide solution (14M).

[0169] Wherein, the particle size distribution of the F type fly ash is as follows: Figure 4 As shown; the mass percentage of each oxide in its chemical composition is: SiO2 (54.17%), Al2O3 (31.57%), Fe2O3 (3.48%), CaO (2.98%), K2O (1.90%), TiO2 (1.37%), MgO (1.22%) and others (3.31%).

[0170] Among them, the sodium silicate solution is produced by Jiashan County Yourui Refractory Materials Co., Ltd., and its chemical composition includes SiO2 accounting for 27.3%, Na2O accounting for 8.54%, and the modulus is 3.3.

[0171] The sodium hydroxide solution is a liquid with a concentration of 14M prepared from solid sodium hydroxide particles with a purity of ≥96%.

[0172] A method for preparing a fly ash-based low-calcium system alkali-activated cementitious material, such as Figure 1 As shown, the following steps are included: (1) Weigh the material according to 100 parts of fly ash using an electronic balance with an accuracy of ±0.01g; (2) Weigh the material according to 27.1 parts of sodium silicate solution and 10.9 parts of sodium hydroxide solution (14M). Use an electronic balance to weigh the material. The weighing balance accuracy of the material is ±0.01g; (3) preparing an alkaline solution by mixing 27.1 parts of sodium silicate solution and 10.9 parts of sodium hydroxide solution (14 M) and stirring until uniform; (4) Pour the alkaline solution prepared in step (3) into the fly ash weighed in step (1), and stir at level 5 for 3 minutes using a stirrer until a completely uniform paste is formed; (5) The alkali-activated gelling material in the paste state obtained by mixing in step (4) is placed into a plastic mold and manually vibrated to squeeze out bubbles.

[0173] (6) The alkali-activated cementitious material of step (5) is placed in a high and low temperature test chamber and cured at a constant temperature of 75°C and a humidity of 35% for 72 hours.

[0174] (7) The alkali-activated cementitious material test blocks cured in step (6) were subjected to compressive strength tests using a YAW-300C fully automatic cement compression and flexural machine in accordance with ASTM C 109–93. The strengths of three test blocks were averaged.

[0175] Since the material used in the blank example is a fly ash-based low-calcium alkali-activated cementitious material, it is named AAF.

[0176] Example 8: The mass parts and test methods of the water reducing agent for low-calcium alkali-activated cementitious materials involved in this example are the same as those of the blank example of compressive strength test, except that 3 parts of silica fume are added. The amount of silica fume to achieve the best fluidity is selected according to the fluidity test results (such as Figure 2 ).

[0177] The silica fume was purchased from the Science and Technology Metallurgical Company and was a spherical white powder with a purity of >99%.

[0178] The above materials are prepared according to the following steps to prepare a water reducing agent suitable for low-calcium system alkali-activated cementitious materials, such as Figure 1 As shown, the following steps are included: (1) Weigh the materials according to 3 parts of silica fume and 100 parts of fly ash. Use an electronic balance to weigh the materials. The weighing accuracy of the material is ±0.01g; (2) Mix the weighed powdered water reducer and the alkali-activated cementitious material precursor - fly ash into a mixer and stir at level 2 speed for 1 minute until uniform; (3) Weigh the materials according to 27.1 parts of sodium silicate solution and 10.9 parts of sodium hydroxide solution (14M). Use an electronic balance to weigh the materials. The weighing accuracy of the material is ±0.01g. (4) preparing an alkaline solution by mixing 27.1 parts of sodium silicate solution and 10.9 parts of sodium hydroxide solution (14 M) and stirring them uniformly; (5) Pour the alkaline solution prepared in step (4) into the fly ash + powdered water reducing agent mixed in step (2), and stir at level 5 for 3 minutes using a mixer until a completely uniform paste is formed; (6) The alkali-activated gelling material prepared in step (4) is placed into a plastic mold and manually vibrated to squeeze out bubbles.

[0179] (7) The alkali-activated cementitious material of step (5) is placed in a high and low temperature test chamber and cured at a constant temperature of 75°C and a humidity of 35% for 72 hours.

[0180] (8) The alkali-activated cementitious material test blocks cured in step (6) were subjected to compressive strength tests using a YAW-300C fully automatic cement compression and flexural machine in accordance with ASTM C 109–93. The strengths of three test blocks were averaged.

[0181] Since the water reducing agent used in the embodiment is silica fume with a dosage of 3%, it is named SFU-3%.

[0182] Comparative Example 36: The mass parts and test methods of the water reducer used for low-calcium alkali-activated cementitious materials in this example are the same as those in the blank example. The test steps are the same as those in the example, except that silica fume is replaced with naphthalene-based water reducer, and the naphthalene-based water reducer is 4 parts. This dosage is selected according to the fluidity test results to achieve the best fluidity dosage of naphthalene-based water reducer (such as Figure 2 ).

[0183] Among them, the naphthalene-based water reducer was purchased from Shanghai Chenqi Chemical Technology Co., Ltd., model number is CQJ-NX, and the appearance is brown-yellow powder.

[0184] Since the water reducer used in Comparative Example 36 is a naphthalene-based water reducer with a dosage of 4%, it is named N-4%.

[0185] Comparative Example 37: The mass parts and test methods of the water reducing agent for low-calcium alkali-activated cementitious materials involved in this example are the same as those of the blank example. The test steps are the same as those of the example, except that silica fume is replaced with borax, and the borax is 4 parts. This dosage is selected according to the fluidity test results to achieve the best fluidity dosage of borax (such as Figure 2 ).

[0186] Among them, borax was purchased from Sinopharm Chemical Reagent Co., Ltd., with the chemical formula of Na2B4O7·10H2O, and is a colorless, transparent crystalline powder.

[0187] Since the water reducing agent used in Comparative Example 37 is borax with a dosage of 4%, it is named B-4%.

[0188] Comparative Example 38: The mass parts and test methods of the water reducing agent for low-calcium alkali-activated cementitious materials involved in this example are the same as those of the blank example. The test steps are the same as those of the example, except that the silica fume is replaced with sodium hexametaphosphate, and the sodium hexametaphosphate is 4 parts. This dosage is selected according to the fluidity test results to achieve the best fluidity of sodium hexametaphosphate (such as Figure 2 ).

[0189] Among them, sodium hexametaphosphate is produced by Xilong Chemical Company, analytically pure, and is in the form of colorless, transparent glass flakes or micro-particle crystals.

[0190] Since the water reducer used in Comparative Example 38 is sodium hexametaphosphate with a dosage of 4%, it is named SH-4%.

[0191] Comparative Example 39: The mass parts and test methods of the water reducing agent for low-calcium alkali-activated cementitious materials involved in this example are the same as those of the blank example. The test steps are the same as those of the example, except that silica fume is replaced with polycarboxylic acid, and the polycarboxylic acid is 0.5 parts. This dosage is selected according to the fluidity test results to achieve the best fluidity dosage of polycarboxylic acid (such as Figure 2 ).

[0192] Among them, polycarboxylic acid was purchased from Shanghai Chenqi Chemical Technology Co., Ltd., Sika brand, model 540P, white solid powder.

[0193] Since the water reducing agent used in Comparative Example 39 is polycarboxylic acid and the content of polycarboxylic acid is 0.5%, it is named PC-0.5%.

[0194] Figure 2 is the result of the liquidity test. Figure 2 It can be seen that the addition of silica fume as a high-efficiency water reducer makes the alkali-activated cementitious material show the most obvious improvement in working performance. At a dosage of 3%, it reaches the optimal expansion of the water reducer-modified alkali-activated cementitious material in the present invention - 222.5mm, which is 40.8% higher than the 158mm of the alkali-activated cementitious material without water reducer. In contrast, naphthalene-based water reducer, borax, sodium hexametaphosphate and polycarboxylic acid increased by 40.2%, 37.6%, 13.3% and 0.8% at 4%, 4%, 4% and 0.5% respectively. Silica sand has no improvement effect at all.

[0195] according to Figure 3 The compressive strength test results show that the addition of silica fume as a high-efficiency water reducer makes the alkali-activated cementitious material show the most obvious improvement in mechanical properties. The compressive strength reaches 58MPa at a 3% dosage, which is 17.3% higher than that of the alkali-activated cementitious material without water reducer. However, the mechanical properties of naphthalene-based water reducer only increase by 11.7% at the optimal fluidity dosage. The rest all reduce the compressive strength of alkali-activated cementitious materials.

[0196] A slag-based high-calcium system alkali-activated cementitious material is formulated according to the following weight parts: (1) 100 parts of S95 grade slag; (2) 14.6 parts of sodium silicate solution; (3) 1.8 parts of sodium hydroxide particles; (4) 18.6 parts of distilled water.

[0197] The S95 grade slag is the only precursor material for preparing alkali-activated cementitious materials, and the particle size distribution is as follows: Figure 4 The mass percentage of each oxide in its chemical composition is: CaO (40.43%), SiO2 (30.46%), Al2O3 (15.81%), MgO (9.42%), Fe2O3 (0.281%), K2O (0.423%), TiO2 (0.673%), MnO (0.52%), Na2O (0.499%), S (1.16%), SrO (0.0549%), Cl (0.0467%), ZrO2 (0.0391%), BaO (0.0389%), P2O5 (0.017%), V2O5 (0.0084%), Y2O3 (0.0083%), CeO2 (0.0069%), CuO (0.0012%).

[0198] Among them, the sodium silicate solution is produced by Jiashan County Yourui Refractory Materials Co., Ltd., and its chemical composition includes SiO2 accounting for 27.3%, Na2O accounting for 8.54%, and the modulus is 3.3.

[0199] Wherein, the sodium hydroxide solution is prepared by using sodium hydroxide solid particles with a purity of ≥96%.

[0200] A method for preparing a slag-based high-calcium system alkali-activated cementitious material, such as Figure 1 As shown, the following steps are included: (1) Weigh the material according to 100 parts of fly ash using an electronic balance with an accuracy of ±0.01g; (2) Weigh the materials according to 14.6 parts of sodium silicate solution, 1.8 parts of sodium hydroxide particles, and 18.6 parts of distilled water. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.01g; (3) preparing an alkaline solution by mixing 14.6 parts of sodium silicate solution, 1.8 parts of sodium hydroxide particles, and 18.6 parts of distilled water and stirring them uniformly; (4) Pour the alkaline solution prepared in step (3) into the slag weighed in step (1), and stir at level 5 for 1 min using a stirrer until a completely uniform paste is formed; (5) Using a cement mortar fluidity tester (referred to as a jump table), the fluidity of the paste-like alkali-activated cementitious material stirred in step (5) is tested in accordance with the ASTM C230 cement mortar fluidity test method.

[0201] Since the material used in this blank example is a slag-based high-calcium system alkali-activated cementitious material, it is named AAS.

[0202] The components, weight parts and testing methods of the water reducing agent for alkali-activated cementitious materials in slag high-calcium system involved in this embodiment are the same as those in the blank example, except that silica fume is added as a water reducing agent, and the amount of silica fume is 0.5 parts.

[0203] The silica fume was purchased from the Science and Technology Metallurgical Company and was a spherical white powder with a purity of >99%.

[0204] The above materials were tested according to the following steps to obtain a water reducing agent suitable for high calcium system alkali-activated cementitious materials, such as Figure 6 As shown, the following steps are included: (1) Weigh the materials according to 0.5 parts of active silica fume and 100 parts of slag. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.01g; (2) Mix the weighed powdered water reducer and the alkali-activated cementitious material precursor - slag into a mixer and stir at level 2 speed for 1 minute until uniform; (3) Weigh the materials according to 14.6 parts of sodium silicate solution, 1.8 parts of sodium hydroxide particles, and 18.6 parts of distilled water. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.01g; (4) preparing an alkaline solution by mixing 14.6 parts of sodium silicate solution, 1.8 parts of sodium hydroxide particles, and 18.6 parts of distilled water and stirring them uniformly; (5) Pour the alkaline solution prepared in step (4) into the slag + powdered water reducer mixed in step (2), and stir at level 5 for 3 minutes using a mixer until a completely uniform paste is formed; (6) Using a cement mortar fluidity tester (referred to as a jump table), the fluidity of the paste-like alkali-activated cementitious material mixed in step (5) is tested in accordance with the ASTM C230 cement mortar fluidity test method.

[0205] Since the water reducing agent used in Example 2-1 is silica fume with a dosage of 0.5%, it is named 2-SFU-0.5%.

[0206] Example 2-2: The components, mass parts and test methods of the water reducer used in the high-calcium system alkali-activated cementitious materials involved in this example are the same as those of the blank example, and the test steps are the same as those of Example 2-1, except that silica fume is added as a water reducer, with the amount of silica fume being 1 part.

[0207] Since the water reducing agent used in Example 2-2 is silica fume with a dosage of 1%, it is named 2-SFU-1%.

[0208] Example 2-3: The components and their mass parts and testing methods of the water reducer used in the high-calcium system alkali-activated cementitious materials involved in this example are the same as those of the blank example, and the testing steps are the same as those of Example 2-1, except that silica fume is added as a water reducer, with the amount of silica fume being 2 parts.

[0209] Since the water reducing agent used in Example 2-3 is silica fume with a dosage of 2%, it is named 2-SFU-2%.

[0210] Example 2-4: The components and their mass parts and testing methods of the water reducer used in the high-calcium system alkali-activated cementitious materials involved in this example are the same as those of the blank example, and the testing steps are the same as those of Example 2-1, except that silica fume is added as a water reducer, with the amount of silica fume being 3 parts.

[0211] Since the water reducing agent used in Example 2-4 is silica fume with a dosage of 3%, it is named 2-SFU-3%.

[0212] Example 2-5: The components and their mass parts and testing methods of the water reducer used in the high-calcium system alkali-activated cementitious materials involved in this example are the same as those of the blank example, and the testing steps are the same as those of Example 2-1, except that silica fume is added as a water reducer, with the amount of silica fume being 4 parts.

[0213] Since the water reducing agent used in Example 2-5 is silica fume with a dosage of 4%, it is named 2-SFU-4%.

[0214] Example 2-6: The components and their mass parts and testing methods of the water reducer used in the high-calcium system alkali-activated cementitious materials involved in this example are the same as those of the blank example, and the testing steps are the same as those of Example 2-1, except that silica fume is added as a water reducer, with the amount of silica fume being 5 parts.

[0215] Since the water reducing agent used in Example 2-6 is silica fume with a dosage of 5%, it is named 2-SFU-5%.

[0216] Example 2-7: The components and their mass parts and testing methods of the water reducer used in the high-calcium system alkali-activated cementitious materials involved in this example are the same as those of the blank example, and the testing steps are the same as those of Example 2-1, except that silica fume is added as a water reducer, with the amount of silica fume being 6 parts.

[0217] Since the water reducing agent used in Example 2-7 is silica fume with a dosage of 6%, it is named 2-SFU-6%.

[0218] Comparative Example 2-1: The weight parts, test steps and methods of the water reducer that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 2-1, except that the silica fume is replaced by a naphthalene-based water reducer.

[0219] Among them, the naphthalene-based water reducer was purchased from Shanghai Chenqi Chemical Technology Co., Ltd., model number is CQJ-NX, and the appearance is brown-yellow powder.

[0220] Since the water reducer used in Comparative Example 1 is a naphthalene-based water reducer with a dosage of 0.5%, it is named 2-N-0.5%.

[0221] Comparative Example 2-2: The weight parts, test steps and methods of the water reducer that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 2-2, except that the silica fume is replaced by a naphthalene-based water reducer.

[0222] Since the water reducer used in Comparative Example 2-2 is a naphthalene-based water reducer with a dosage of 1%, it is named 2-N-1%.

[0223] Comparative Example 2-3: The weight parts, test steps and methods of the water reducer that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-3, except that the silica fume is replaced by a naphthalene-based water reducer.

[0224] Since the water reducer used in Comparative Example 2-3 is a naphthalene-based water reducer with a dosage of 2%, it is named 2-N-2%.

[0225] Comparative Example 2-4: The weight parts, test steps and methods of the water reducer that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-4, except that the silica fume is replaced by a naphthalene-based water reducer.

[0226] Since the water reducer used in Comparative Example 2-4 is a naphthalene-based water reducer with a dosage of 3%, it is named 2-N-3%.

[0227] Comparative Example 2-5: The weight parts, test steps and methods of the water reducer that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-5, except that the silica fume is replaced by a naphthalene-based water reducer.

[0228] Since the water reducer used in Comparative Example 2-5 is a naphthalene-based water reducer with a dosage of 4%, it is named 2-N-4%.

[0229] Comparative Example 2-6: The weight parts, test steps and methods of the water reducer that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-6, except that the silica fume is replaced by a naphthalene-based water reducer.

[0230] Since the water reducer used in Comparative Example 2-6 is a naphthalene-based water reducer with a dosage of 5%, it is named 2-N-5%.

[0231] Comparative Example 2-7: The weight parts, test steps and methods of the water reducer that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-7, except that the silica fume is replaced by a naphthalene-based water reducer.

[0232] Since the water reducer used in Comparative Example 2-7 is a naphthalene-based water reducer with a dosage of 6%, it is named 2-N-6%.

[0233] Comparative Example 2-8: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 2-1, except that the silica fume is replaced by borax.

[0234] Among them, borax was purchased from Sinopharm Chemical Reagent Co., Ltd., with the chemical formula of Na2B4O7·10H2O, and is a colorless, transparent crystalline powder.

[0235] Since the water reducing agent used in Comparative Example 2-8 is borax with a dosage of 0.5%, it is named 2-B-0.5%.

[0236] Comparative Example 2-9: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 2-2, except that the silica fume is replaced by borax.

[0237] Since the water reducing agent used in Comparative Example 2-9 is borax with a dosage of 1%, it is named 2-B-1%.

[0238] Comparative Example 2-10: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-3, except that the silica fume is replaced by borax.

[0239] Since the water reducing agent used in Comparative Example 2-10 is borax with a dosage of 2%, it is named 2-B-2%.

[0240] Comparative Example 2-11: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-4, except that the silica fume is replaced by borax.

[0241] Since the water reducing agent used in Comparative Example 2-11 is borax with a dosage of 3%, it is named 2-B-3%.

[0242] Comparative Example 2-12: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-5, except that the silica fume is replaced by borax.

[0243] Since the water reducing agent used in Comparative Example 2-12 is borax with a dosage of 4%, it is named 2-B-4%.

[0244] Comparative Example 2-13: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-6, except that the silica fume is replaced by borax.

[0245] Since the water reducing agent used in Comparative Example 2-13 is borax with a dosage of 5%, it is named 2-B-5%.

[0246] Comparative Example 2-14: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-7, except that the silica fume is replaced by borax.

[0247] Since the water reducing agent used in Comparative Example 2-14 is borax with a dosage of 6%, it is named 2-B-6%.

[0248] Comparative Example 2-15: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 2-1, except that the silica fume is replaced with sodium hexametaphosphate.

[0249] Among them, sodium hexametaphosphate is produced by Xilong Chemical Company, analytically pure, and is in the form of colorless, transparent glass flakes or micro-particle crystals.

[0250] Since the water reducing agent used in Comparative Example 2-15 is sodium hexametaphosphate with a dosage of 0.5%, it is named 2-SH-0.5%.

[0251] Comparative Example 2-16: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-2, except that the silica fume is replaced with sodium hexametaphosphate.

[0252] Since the water reducing agent used in Comparative Example 2-16 is sodium hexametaphosphate with a dosage of 1%, it is named 2-SH-1%.

[0253] Comparative Example 2-17: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-3, except that the silica fume is replaced with sodium hexametaphosphate.

[0254] Since the water reducing agent used in Comparative Example 2-17 is sodium hexametaphosphate and the dosage is 2%, it is named 2-SH-2%.

[0255] Comparative Example 2-18: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-4, except that the silica fume is replaced with sodium hexametaphosphate.

[0256] Since the water reducing agent used in Comparative Example 2-18 is sodium hexametaphosphate with a dosage of 3%, it is named 2-SH-3%.

[0257] Comparative Example 2-19: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-5, except that the silica fume is replaced with sodium hexametaphosphate.

[0258] Since the water reducing agent used in Comparative Example 2-19 is sodium hexametaphosphate with a dosage of 4%, it is named 2-SH-4%.

[0259] Comparative Example 2-20: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-6, except that the silica fume is replaced with sodium hexametaphosphate.

[0260] Since the water reducing agent used in Comparative Example 2-20 is sodium hexametaphosphate and the dosage is 5%, it is named 2-SH-5%.

[0261] Comparative Example 2-21: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-7, except that the silica fume is replaced with sodium hexametaphosphate.

[0262] Since the water reducing agent used in Comparative Example 2-21 is sodium hexametaphosphate with a dosage of 6%, it is named 2-SH-6%.

[0263] Comparative Example 2-22: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 2-1, except that the silica fume is replaced by polycarboxylic acid.

[0264] Among them, polycarboxylic acid was purchased from Shanghai Chenqi Chemical Technology Co., Ltd., Sika brand, model 540P, white solid powder.

[0265] Since the water reducer used in Comparative Example 2-22 is polycarboxylic acid with a dosage of 0.5%, it is named 2-PC-0.5%.

[0266] Comparative Example 2-23: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-2, except that the silica fume is replaced by polycarboxylic acid.

[0267] Since the water reducer used in Comparative Example 2-23 is polycarboxylic acid with a dosage of 1%, it is named 2-PC-1%.

[0268] Comparative Example 2-24: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-3, except that the silica fume is replaced by polycarboxylic acid.

[0269] Since the water reducer used in Comparative Example 2-24 is polycarboxylic acid with a dosage of 2%, it is named 2-PC-2%.

[0270] Comparative Example 2-25: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-4, except that the silica fume is replaced by polycarboxylic acid.

[0271] Since the water reducer used in Comparative Example 2-25 is polycarboxylic acid with a dosage of 3%, it is named 2-PC-3%.

[0272] Comparative Example 2-26: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-5, except that the silica fume is replaced by polycarboxylic acid.

[0273] Since the water reducer used in Comparative Example 2-26 is polycarboxylic acid with a dosage of 4%, it is named 2-PC-4%.

[0274] Comparative Example 2-27: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-6, except that the silica fume is replaced by polycarboxylic acid.

[0275] Since the water reducer used in Comparative Example 2-27 is polycarboxylic acid with a dosage of 5%, it is named 2-PC-5%.

[0276] Comparative Example 2-28: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-7, except that the silica fume is replaced by polycarboxylic acid.

[0277] Since the water reducer used in Comparative Example 2-28 is polycarboxylic acid with a dosage of 6%, it is named 2-PC-6%.

[0278] Comparative Example 2-29: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those in Example 2-1, except that the silica fume is replaced by silica sand.

[0279] The silica sand was purchased from Beasley New Materials Company, with a purity of >99% and a white spherical powder.

[0280] Since the water reducing agent used in Comparative Example 2-29 is silica sand with a dosage of 0.5%, it is named 2-SFL-0.5%.

[0281] Comparative Example 2-30: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-2, except that the silica fume is replaced by silica sand.

[0282] Since the water reducing agent used in Comparative Example 2-30 is silica sand with a dosage of 1%, it is named 2-SFL-1%.

[0283] Comparative Example 2-31: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-3, except that the silica fume is replaced by silica sand.

[0284] Since the water reducing agent used in Comparative Example 2-31 is silica sand with a dosage of 2%, it is named 2-SFL-2%.

[0285] Comparative Example 2-32: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-4, except that the silica fume is replaced by silica sand.

[0286] Since the water reducing agent used in Comparative Example 2-32 is silica sand with a dosage of 3%, it is named 2-SFL-3%.

[0287] Comparative Example 2-33: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-5, except that the silica fume is replaced by silica sand.

[0288] Since the water reducing agent used in Comparative Example 2-33 is silica sand with a dosage of 4%, it is named 2-SFL-4%.

[0289] Comparative Example 2-34: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-6, except that the silica fume is replaced by silica sand.

[0290] Since the water reducing agent used in Comparative Example 2-34 is silica sand with a dosage of 5%, it is named 2-SFL-5%.

[0291] Comparative Example 2-35: The weight parts, test steps and methods of the water reducing agent that can be used for high-calcium system alkali-activated cementitious materials involved in this embodiment are the same as those of Example 2-7, except that the silica fume is replaced by silica sand.

[0292] Since the water reducing agent used in Comparative Example 2-35 is silica sand with a dosage of 6%, it is named 2-SFL-6%.

[0293] A slag-based high-calcium system alkali-activated cementitious material is formulated according to the following weight parts: (1) 100 parts of S95 grade slag; (2) 14.6 parts of sodium silicate solution; (3) 1.8 parts of sodium hydroxide particles; (4) 18.6 parts of distilled water.

[0294] The S95 grade slag is the only precursor material for preparing alkali-activated cementitious materials, and the particle size distribution is as follows: Figure 4 As shown; the mass percentage of each oxide in its chemical composition is: CaO (40.43%), SiO2 (30.46%), Al2O3 (15.81%), MgO (9.42%), Fe2O3 (0.281%), K2O (0.423%), TiO2 (0.673%), MnO (0.52%), Na2O (0.499%), S (1.16%), SrO (0.0549%), Cl (0.0467%), ZrO2 (0.0391%), BaO (0.0389%), P2O5 (0.017%), V2O5 (0.0084%), Y2O3 (0.0083%), CeO2 (0.0069%), and CuO (0.0012%).

[0295] Among them, the sodium silicate solution is produced by Jiashan County Yourui Refractory Materials Co., Ltd., and its chemical composition includes SiO2 accounting for 27.3%, Na2O accounting for 8.54%, and the modulus is 3.3.

[0296] The sodium hydroxide particles are used to prepare the alkaline excitation solution, the purity of which is ≥96%, and are purchased from Tianjin Fengchuan Company.

[0297] Among them, distilled water is used to prepare alkaline excitation solution, Putian Yuxin Water Treatment Equipment Co., Ltd.

[0298] A method for preparing a slag-based high-calcium system alkali-activated cementitious material, such as Figure 6 As shown, the following steps are included: (1) Weigh the material according to 100 parts of slag using an electronic balance with an accuracy of ±0.01g; (2) Weigh the materials according to 14.6 parts of sodium silicate solution, 1.8 parts of sodium hydroxide particles, and 18.6 parts of distilled water. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.01g; (3) preparing an alkaline solution by mixing 14.6 parts of sodium silicate solution, 1.8 parts of sodium hydroxide particles, and 18.6 parts of distilled water and stirring them uniformly; (4) Pour the alkaline solution prepared in step (3) into the slag weighed in step (1), and stir at level 5 for 1 min using a stirrer until a completely uniform paste is formed; (5) The alkali-activated gelling material in the paste state obtained by mixing in step (4) is placed into a plastic mold and manually vibrated to squeeze out bubbles.

[0299] (6) According to European standard EN 196-1, the alkali-activated cementitious material of step (5) is placed in a standard curing room with a constant room temperature (20±2°C) and a humidity of 99% for curing for 28 days.

[0300] (7) The alkali-activated cementitious material test blocks cured in step (6) were subjected to compressive strength tests using a YAW-300C fully automatic cement compression and flexural machine in accordance with ASTM C 109–93. The strengths of three test blocks were averaged.

[0301] Since the material used in the blank example is slag-based alkali activated cementitious material, it is named AAS.

[0302] Example 2-8: The mass parts and test methods of the water reducing agent for high calcium system alkali-activated cementitious materials involved in this example are the same as those of the blank example, except that 3 parts of silica fume are added. The amount of silica fume to achieve the best fluidity is selected according to the fluidity test results (such as Figure 7 ).

[0303] The silica fume was purchased from the Science and Technology Metallurgical Company and was a spherical white powder with a purity of >99%.

[0304] The above materials are prepared according to the following steps to prepare a water reducing agent suitable for high calcium system alkali-activated cementitious materials, such as Figure 6 As shown, the following steps are included: (1) Weigh the materials according to 0.5 parts of silica fume and 100 parts of slag. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.01g; (2) Mix the weighed powdered water reducer and the alkali-activated cementitious material precursor - slag into a mixer and stir at level 2 speed for 1 minute until uniform; (3) Weigh the materials according to 14.6 parts of sodium silicate solution, 1.8 parts of sodium hydroxide particles, and 18.6 parts of distilled water. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.01g; (4) preparing an alkaline solution by mixing 14.6 parts of sodium silicate solution, 1.8 parts of sodium hydroxide particles, and 18.6 parts of distilled water and stirring them uniformly; (5) Pour the alkaline solution prepared in step (4) into the slag + powdered water reducer mixed in step (2), and stir at level 5 for 3 minutes using a mixer until a completely uniform paste is formed; (6) The alkali-activated gelling material in the paste state obtained by mixing in step (5) is placed into a plastic mold and manually vibrated to squeeze out bubbles.

[0305] (7) According to European standard EN 196-1, the alkali-activated cementitious material of step (6) is placed in a standard curing room at a constant room temperature (20±2°C) and a humidity of 99% for curing for 28 days.

[0306] (8) The alkali-activated cementitious material test blocks cured in step (7) were subjected to compressive strength tests using a YAW-300C fully automatic cement compression and flexural machine in accordance with ASTM C 109–93. The strengths of three test blocks were averaged.

[0307] Since the water reducing agent used in the embodiment is silica fume with a dosage of 3%, it is named 2-SFU-3%.

[0308] Comparative Example 2-36: The mass parts and test methods of the water reducer used in the high calcium system alkali activated cementitious material in this example are the same as those in the blank example. The test steps are the same as those in the example, except that the silica fume is replaced with a naphthalene-based water reducer, and the naphthalene-based water reducer is 3 parts. The dosage of the naphthalene-based water reducer is selected according to the fluidity test results to achieve the best fluidity (such as Figure 7 ).

[0309] Among them, the naphthalene-based water reducer was purchased from Shanghai Chenqi Chemical Technology Co., Ltd., model number is CQJ-NX, and the appearance is brown-yellow powder.

[0310] Since the water reducer used in Comparative Example 2-36 is a naphthalene-based water reducer with a dosage of 2%, it is named 2-N-2%.

[0311] Comparative Example 2-37: The mass parts and test methods of the water reducing agent for high calcium system alkali-activated cementitious materials involved in this example are the same as those of the blank example. The test steps are the same as those of the example, except that silica fume is replaced with borax, and the borax is 5 parts. This dosage is selected according to the fluidity test results to achieve the best fluidity dosage of borax (such as Figure 7 ).

[0312] Among them, borax was purchased from Sinopharm Chemical Reagent Co., Ltd., with the chemical formula of Na2B4O7·10H2O, and is a colorless, transparent crystalline powder.

[0313] Since the water reducing agent used in Comparative Example 2-37 is borax with a dosage of 5%, it is named 2-B-5%.

[0314] Comparative Example 2-38: The mass parts and test methods of the water reducing agent for high calcium system alkali-activated cementitious materials involved in this example are the same as those of the blank example. The test steps are the same as those of the example, except that the silica fume is replaced with sodium hexametaphosphate, and the sodium hexametaphosphate is 2 parts. This dosage is selected according to the fluidity test results to achieve the best fluidity of sodium hexametaphosphate (such as Figure 7 ).

[0315] Among them, sodium hexametaphosphate is produced by Xilong Chemical Company, analytically pure, and is in the form of colorless, transparent glass flakes or micro-particle crystals.

[0316] Since the water reducing agent used in Comparative Example 2-38 is sodium hexametaphosphate and the dosage is 2%, it is named 2-SH-2%.

[0317] Comparative Example 2-39: The mass parts and test methods of the water reducing agent for high calcium system alkali-activated cementitious materials involved in this example are the same as those of the blank example. The test steps are the same as those of the example, except that silica fume is replaced with polycarboxylic acid, and the polycarboxylic acid is 1 part. This dosage is selected according to the fluidity test results to achieve the best fluidity dosage of polycarboxylic acid (such as Figure 7 ).

[0318] Among them, polycarboxylic acid was purchased from Shanghai Chenqi Chemical Technology Co., Ltd., Sika brand, model 540P, white solid powder.

[0319] Since the water reducing agent used in Comparative Example 2-39 is polycarboxylic acid and the polycarboxylic acid is 1%, it is named 2-PC-1%.

[0320] Figure 7 The results of fluidity test. It can be seen from the figure that the addition of silica fume as a high-efficiency water reducer makes the alkali-activated cementitious material show the most obvious improvement in working performance. At a dosage of 2%, it reaches the optimal expansion of 236mm for water reducer-modified alkali-activated cementitious material in the present invention, which is 30% higher than the 181.5mm of alkali-activated cementitious material without water reducer. In contrast, naphthalene-based water reducer, borax, sodium hexametaphosphate and polycarboxylic acid increased by 9.7%, 15.7%, 5.8% and 1.9% at 2%, 3%, 1% and 1% respectively. Silica sand has no improvement effect at all.

[0321] according to Figure 8The compressive strength test results show that the addition of silica fume as a high-efficiency water reducer allows the high-calcium system alkali-activated cementitious materials to maintain the original mechanical properties while also having a small improvement. When the addition amount is 2%, although the compressive strength is lower than that of the slag alkali-activated cementitious materials after only one day of curing, the compressive strength after three days is slightly improved compared with the slag alkali-activated cementitious materials, and the final 28d compressive strength reaches 104.6MPa. The rest all reduce the compressive strength of the alkali-activated cementitious materials.

[0322] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A use of silica fume as a water reducing agent, characterized in that: The water reducing agent is used for a low-calcium-alkali activated cementitious material system and / or a high-calcium-alkali activated cementitious material system.

2. The use of silica fume as a water reducing agent according to claim 1, characterized in that: The low-calcium alkali activated cementitious material system is a fly ash-based low-calcium alkali activated cementitious material system and / or the high-calcium high-calcium alkali activated cementitious material system is a slag-based high-calcium alkali activated cementitious material system.

3. The use of silica fume as a water reducer according to claim 2, wherein the fly ash in the low-calcium system is Class F fly ash, which is the only precursor material for preparing low-calcium system alkali-activated cementitious materials, and the mass percentage of each oxide in the chemical composition of the Class F fly ash is: SiO2 is 54.17%, Al2O3 is 31.57%, Fe2O3 is 3.48%, CaO is 2.98%, K2O is 1.90%, TiO2 is 1.37%, MgO is 1.22% and others are 3.31%.

4. The use of silica fume as a water reducing agent according to claim 2, wherein the S95 grade slag is the only precursor material for preparing a high calcium system alkali-activated cementitious material, and the mass percentage of each oxide in the chemical composition of the S95 grade slag is: CaO is 40.43%, SiO2 is 30.46%, Al2O3 is 15.81%, MgO is 9.42%, Fe2O3 is 0.281%, K2O is 0.423%, TiO 2 is 0.673%, MnO is 0.52%, Na2O is 0.499%, S is 1.16%, SrO is 0.0549%, Cl is 0.0467%, ZrO2 is 0.0391%, BaO is 0.0389%, P2O5 is 0.017%, V2O5 is 0.0084%, Y2O3 is 0.0083%, CeO2 is 0.0069%, and CuO is 0.0012%.

5. A fly ash-based low-calcium system alkali-activated cementitious material with silica fume as a water reducer, characterized in that: The alkali-activated cementitious material is prepared from the following materials: a water reducing agent, the only precursor material of the alkali-activated cementitious material - F-type fly ash, and an alkali solution; the water reducing agent is silica fume.

6. The fly ash-based low-calcium alkali-activated cementitious material according to claim 5, characterized in that: The alkaline solution includes sodium silicate solution and sodium hydroxide solution. The water reducer is 0.01-12 parts by weight, the alkali-activated cementitious material precursor material - Class F fly ash is 80-150 parts, the sodium silicate solution is 20-35 parts, and the sodium hydroxide solution is 8-15 parts.

7. The fly ash-based low-calcium system alkali-activated cementitious material with silica fume as a water reducer according to claim 6, characterized in that: The sodium silicate solution comprises 27.3% SiO2, 8.54% Na2O and a modulus of 3.3; the sodium hydroxide solution is a liquid having a concentration of 10-20M and is prepared from solid sodium hydroxide particles having a purity of ≥96%.

8. The fly ash-based low-calcium system alkali-activated cementitious material with silica fume as a water reducer according to claim 6, characterized in that: The Class F fly ash is the only precursor material for preparing alkali-activated cementitious materials. The mass percentages of the oxides in the chemical composition of the Class F fly ash are: SiO2 is 54.17%, Al2O3 is 31.57%, Fe2O3 is 3.48%, CaO is 2.98%, K2O is 1.90%, TiO2 is 1.37%, MgO is 1.22% and others are 3.31%.

9. A fly ash-based low-calcium system alkali-activated cementitious material with silica fume as a water reducer according to any one of claims 5 to 8, characterized in that: The alkali-activated gelling material has an expansion of not less than 200 mm.

10. A method for preparing a fly ash-based low-calcium alkali-activated cementitious material according to any one of claims 5 to 9, characterized in that: The steps include: (1) Weigh the water reducer and the only precursor material of alkali-activated cementitious material - Class F fly ash according to the mass fraction; (2) Mix the water reducing agent and the alkali-activated cementitious material precursor material - Class F fly ash into a mixer and stir until uniform; (3) weighing a sodium silicate solution and a sodium hydroxide solution according to their mass fractions; wherein the chemical composition of the sodium silicate solution is 27.3% SiO2, 8.54% Na2O, and the modulus is 3.3; (4) preparing an alkaline solution by mixing the sodium silicate solution and the sodium hydroxide solution in step (3) and stirring them uniformly; (5) Pour the alkaline solution prepared in step (4) into the fly ash and silica ash mixed in step (2), and stir until uniform using a mixer.

11. A slag-based high-calcium system alkali-activated cementitious material with silica fume as a water reducer, characterized in that: The alkali-activated cementitious material is prepared from the following materials: a water reducing agent, the only precursor material of the alkali-activated cementitious material - S95 grade slag, and an alkali solution; the water reducing agent is silica fume.

12. The slag-based high-calcium system alkali-activated cementitious material with silica fume as a water reducer according to claim 11, characterized in that: The alkaline solution comprises a sodium silicate solution and a sodium hydroxide solution. In parts by mass, the water reducer is 0.01-12 parts, the alkali-activated cementitious material precursor material - S95 grade slag is 80-150 parts, the sodium silicate solution is 10-25 parts, the sodium hydroxide solid particles are 4-10 parts, and the distilled water is 10-16 parts.

13. The slag-based high-calcium system alkali-activated cementitious material with silica fume as a water reducer according to claim 11, characterized in that: The sodium silicate solution contains 27.3% SiO2 and 8.54% Na2O, and the modulus is 3.3; the purity of the sodium hydroxide solid particles is ≥96%.

14. The slag-based high-calcium system alkali-activated cementitious material with silica fume as a water reducer according to claim 11, characterized in that: The S95-grade slag is the only precursor material for preparing slag-based high-calcium system alkali-activated cementitious materials. The mass percentages of the oxides in the chemical composition of the S95-grade slag are: CaO is 40.43%, SiO2 is 30.46%, Al2O3 is 15.81%, MgO is 9.42%, Fe2O3 is 0.281%, K2O is 0.423%, TiO2 is 0.673%, MnO is 0.52%, Na2O is 0.499%, S is 1.16%, SrO is 0.0549%, Cl is 0.0467%, ZrO2 is 0.0391%, BaO is 0.0389%, P2O5 is 0.017%, V2O5 is 0.0084%, Y2O3 is 0.0083%, CeO2 is 0.0069%, and CuO is 0.0012%.

15. A slag-based high-calcium system alkali-activated cementitious material with silica fume as a water reducer according to any one of claims 11 to 14, characterized in that: The alkali activated gelling material has an expansion of 190-200 mm.

16. A method for preparing a slag-based high-calcium system alkali-activated cementitious material with silica fume as a water reducer as claimed in any one of claims 11 to 14, characterized in that: The steps include: (1) Weigh the water reducer and the alkali activated cementitious material precursor material - S95 grade slag according to the mass fraction; (2) Mix the water reducing agent and the precursor material of the alkali-activated cementitious material - S95 grade slag into a mixer and stir until uniform; (3) weighing a sodium silicate solution and a sodium hydroxide solution according to their mass fractions; wherein the chemical composition of the sodium silicate solution is 27.3% SiO2, 8.54% Na2O, and the modulus is 3.3; (4) preparing an alkaline solution by mixing the sodium silicate solution and the sodium hydroxide solution in step (3) and stirring them uniformly; (5) Pour the alkaline solution prepared in step (4) into the fly ash and silica fume water reducer mixed in step (2), and stir until uniform using a mixer.

Citation Information

Cited By

  • Use of silica fume as water-reducing agent and corresponding alkali-activated cementitious materials and preparation methods

    WO2026036793A1